A copper-doped nickel oxide bilayer for enhancing efficiency and stability of hysteresis-free inverted mesoporous perovskite solar cells. (October 2017) - Yao, Kai; Li, Fan; He, Qiqi; Wang, Xiaofeng; Jiang, Yihua; Huang, Haitao; Jen, Alex K.-Y.
Abstract: Although the inverted perovskite solar cells (PeSCs) have many advantages such as simple device fabrication, high stability and small hysteresis, the efficiency of inverted mesoporous PeSCs are still lower than those of normal-structure. For developing inverted mesoporous perovskite solar cells and the future design of tandem devices, a p-type metal oxide with high surface area and good charge carrier mobility is of paramount importance. Here, we develop a bilayer structure of p-type Cu:NiOx nanoparticle-based mesoporous and Cu-doped NiOx blocking layers to achieve efficient charge collection at the NiOx /perovskite interface with minimized recombination loss. Our strategy enables the fabrication of centimeter-sized perovskite solar cells with a decent efficiency of 18.1%, significantly improved stability, and negligible hysteresis. The rational design of the p-type Cu-doped metal oxide bilayer provides an effective strategy for future development of inverted architecture based mesoporous solar cells. Graphical abstract: